PENGEMBANGAN MEDIA PEMBELAJARAN APLIKASI IQRO BERBASIS SMARTPHONE ANDROID UNTUK MENINGKATKAN KEMAMPUAN MENGENAL HURUF HIJAIYAH BAGI ANAK USIA DINI - Annisa Dwi Nur Rahmawati, - (2021)
Thesis Department of Education Curriculum and Technology, Faculty of Education, Indonesian Education University in 2019. Learning media can be an intermediary for delivering messages between communicants and communicators. Learning media also has a role in achieving the indicators that have been prepared. The learning media itself has supporting factors to suit the needs of teachers and students. The purpose of this research is to develop android-based learning media based on the analysis conducted at Daarut Tauhiid Kindergarten, to design and develop learning media, and to reflect on the assessments and responses of experts and users of the developed application. This study uses the design and development (D&D) method with the ADDIE educational product development model (Analysis, Design, Development, Implementation, and Evaluation). The instrument in this study was a questionnaire given to users after using the iqro application media. The assessment was carried out on two categories of assessment by material experts and media experts. The media expert's assessment results show that the product developed is declared feasible with an average value of 80% and is classified as "very good". The results of the material expert assessment show that the product developed is declared feasible with an average value of 80% and is classified as "very good". The product that has been developed is then tested on users, namely Daarut Tauhiid Kindergarten students. The assessment was carried out on three aspects, namely aspects of content quality, language, and media quality. The user research results show that the iqro application product developed gets an average value of 85.27% and is classified as "very good" so that the iqro application media is feasible to use.